Second Generation Challenges in Decentralisation: Learnings From Kerala - S.M Vijayanand (KILA Journal of Local Governance, 2013)
After the passage of the 73 rd and 74 th Amendments to the Constitution, Kerala carried out pioneering reforms and set out on the path of rapid and wide ranging decentralization. Fifteen years of decentralization in Kerala has resulted in substantial achievements even while throwing up major challenges that call for immediate intervention. This paper, based on the learnings from Kerala, provides a vivid account of second generation challenges in decentralization.